On-line monitoring of the sol-gel transition temperature of thermosensitive chitosan/β-glycerophosphate hydrogels by low field NMR. (15th June 2020) - Chen, Fangyu; Chen, Chao; Zhao, Dawei; Zhang, Songping; Ma, Guanghui; Su, Zhiguo; Li, Xiunan
Highlights: Thermosensitive hydrogels were studied by a temperature controlled LF-NMR system. Microstructure changes of hydrogels can be non-destructively identified by T2 . The hydrogel gelation temperature was monitored in situ through measuring T2 . Abstract: A temperature controlled low field nuclear magnetic resonance (LF-NMR) T2 relaxometry technique based on the mobility changes of water trapped in hydrogels, was successfully used for on-line determination of the sol-gel transition temperature for chitosan/β-glycerophosphate (CS/GP) hydrogels in real time. The LF-NMR results indicated that the gelation temperature decreased gradually with increasing GP concentration, and the results were supported by both thermogravimetric differential scanning calorimetry (DSC) and rheological findings; however, LF-NMR allows non-destructive monitoring of samples during continuous heating. Moreover, as the mobility of water molecules varies greatly during the sol-gel phase transition, the LF-NMR measurement was more sensitive and accurate (RSD ≤ 0.1 %, n = 5) compared with DSC (RSD: 1.2 %–3.7 %, n = 5) and rheology (RSD: 1.1 %–2.3 %, n = 5).